Semilocal analysis of equations with smooth operators - George J. Miel (International Journal of Mathematics and Mathematical Sciences)
Recent work on semilocal analysis of nonlinear operator equations is informally reviewed. A refined version of the Kantorovich theorem for Newton's method, with new error bounds, is presented. Related topics are briefly surveyed.